How stable is the underlying process of stock prices? Empirical evidence of structural breaks in the firm-level dividend of the U.S. firms - Mazlan, Nur Syazwani; Bulkley, George (Faculty of Economics and Management, Universiti Putra Malaysia, 2015)
In this paper, we present empirical evidence of instability in the form of structural breaks in dividend at the firm level of the U.S. firms. We perform the Bai and Perron (2003) structural break program that estimates multiple breaks based on deterministic econometric approach. We also observe for links between any specific episodes in the economic and financial history of the U.S and structural breaks detected in the dividend process of the U.S firms.